Diversifikasi Hasil Panen Tanaman Obat Keluarga (TOGA) Menjadi Produk Pangan Fungsional di Dusun Numpukan - Eni Kartika Sari; Danang Yulianto; Rini Sulistyawati (Humanism: Journal of Community Empowerment (HJCE), 2020)
The Community Service Program (PKM) have been carried out which aim to process the yield of Family Medicinal Plants (TOGA) into functional food products which high economic value in Numpukan, Karangtengah, Imogiri, Bantul. The method used is socialization and training. The socialization was carried out to increase the awareness of the people of Numpukan, Karangtengah in the importance of processing of the TOGA harvest into functional food. The training on making secang syrup and spiced ice cream was carried out to improve community skills. According to the initial plan, this PKM activity produced two functional food products namely secang syrup and spiced ice cream which are ready to be marketed. The marketing mechanism is through exhibitions and is marketed directly in stalls around Numpukan, Karangtengah. During the implementation of PKM, the products of the community of Numpukan Village were exhibited twice by the PKM team with a significant market response.Keywords : Functional Food Products, Product Marketing, Economic Value Increasing